Keputusan Pembelian: Pengaruh Persepsi Kualitas Produk dan Kepercayaan - Reyza Banowati; Lailati Nisrokha; Sawsan Arif Sya’bani; Khairani Zikrinawati; Zulfa Fahmy (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to see whether or not there is an influence of product quality on consumer decisions in buying clothes on the Shopee App, to see how trust affects consumer decisions in buying clothes in the Shopee App, and to see the influence between product quality and trust in clothing purchasing decisions in the Shopee App. The sample used was 150 respondents with the purposive sampling method. The data obtained was obtained by filling out a questionnaire by the respondent. The results showed that simultaneous or partial 1) product quality had an influence on the purchase decision as evidenced by the value of t counted 7.717 > t table 1.976, 2) confidence affects the purchase decision with a value of t count 4.335 > t table 1.976, while the results of the test F showed F count 73.398 > F table 3.0 This means that product quality and trust simultaneously affect purchasing decisions through the Shopee App. Through the calculation of the determination coefficient, it is proven that R Square is 50% which is in the sufficient category, the conclusion obtained 3) product quality and trust simultaneously there is an influence 50% on the purchase decision through the Shopee Application while the remaining 50% is the influence of other variables that are not included in this study.